Simmel and Beyond The Contemporary Relevance of Simmel’s Thought - Pedro Caetano; Maria Manuela Mendes (2022)
Bringing together the work of scholars from across Europe, this book shows how Simmel's categories can be used to explore contemporary issues and further shed light on trends characteristic of global modernity. Thematically organised around the major societal challenges currently faced by developed countries – those of making societies that are inclusive, reflexive and creative, sustainable, and democratic societies – it examines diverse phenomena, such as living in an increasingly multicultural societies, the social exclusion of vulnerable ethnic groups, the increasing concern with cyberbullying, the need to fight climate change, the rise of political populism, and the recruitment of youths from western countries to Islamic religious fundamentalism. Drawing on Simmel’s sociological theory and expounding new approaches to research inspired by his work, this volume emphasises the conceptual pillars of Simmelian thought, meanings, processes, and forms. As such, it will appeal to scholars of sociology and social theory with interests in the work of Simmel and its contemporary relevance.